Internal entry of ribosomes is directed by the 5' noncoding region of classical swine fever virus and is dependent on the presence of an RNA pseudoknot upstream of the initiation codon. - Rijnbrand, R (1997)
Bicistronic RNAs containing the 373-nucleotide-long 5' nontranslated region (NTR) of the classical swine fever virus (CSFV) genome as intercistronic spacer were used to show the presence of an internal ribosome entry site (IRES) in the 5' end of the CSFV genome. By coexpression of the poliovirus 2A protease it was demonstrated that the CSFV 5' NTR-driven translation is independent of the presence of functional eukaryotic initiation factor eIF-4F. Deletion analysis indicated that the 5' border of the IRES is located between nucleotides 28 and 66. The role of a proposed pseudoknot structure at the 3' end of the CSFV 5' NTR in IRES-mediated translation was investigated by site-directed mutagenesis. Mutant RNAs that had lost the ability to base pair in stem II of the pseudoknot were translationally inactive. Translation to wild-type levels could be restored through the introduction of compensatory complementary base changes that repaired base pairing in stem II. In addition, we showed that the AUG codon, which is located 7 nucleotides upstream of the polyprotein initiation site and is conserved in pestiviruses, could not be used to initiate translation. Also, an AUG codon introduced downstream of the polyprotein initiation site was not recognized as an initiation site by ribosomes. These data suggest that after internal entry on the CSFV 5' NTR, ribosomal scanning for the initiation codon is limited to a small region.